Thoracentesis for the Diagnosis and Management of Pleural Effusions: The Current State of a Centuries-Old Procedure - Michael J. Nicholson; Christopher Manley; Danish Ahmad (MDPI AG, 2023)
Thoracentesis is a fundamental procedure in interventional pulmonology, providing both diagnostic and therapeutic value. This review article offers a comprehensive analysis of thoracentesis, delving into pleural anatomy, procedural techniques, indications, and recent advancements. The article details the evolution of thoracentesis, including the crucial role of ultrasound guidance and emerging approaches that enhance precision and minimize complications. It addresses the wide range of indications for thoracentesis in diverse clinical scenarios, from the diagnosis of pleural effusions to therapeutic drainage of pleural collections. Furthermore, this review explores the management of coagulopathy and anticoagulation pertaining to thoracentesis. It will also provide strategies for preventing and managing complications, ensuring that thoracentesis remains a well-tolerated procedure with minimal risks. This article concludes by examining future directions in thoracentesis, including potential innovations and trends that will shape the landscape of interventional pulmonary medicine. This review serves as an essential resource for pulmonologists, interventional radiologists, and healthcare professionals, offering a comprehensive update on thoracentesis.